A Study Paper on Forest Fire Detection Using Wireless Sensor Network - Kanniga, E.; S Jadhav, Purushottam (International Journal of Psychosocial Rehabilitation, 2019)
This article presents the design of a system for monitoring temperature and humidity for the prevention of forest fires using wireless sensor networks. An initial study of the causes of Forest Fires, like how to prevent them, is necessary have a clear idea of how to implement a valid network design that is capable of detecting possible changes in the environment; in that way we can prevent a disaster (Forest fire) that could lead to loss of a significant number of natural resources